Anisotropic thermal properties of an argillaceous rock under elevated temperatures and external load conditions. (February 2023) - Yu, Hongdan; Lu, Chen; Liu, Wei; Chen, Weizhong; Li, Honghui; Huang, Jiawei
Abstract: The design and long-term safety of geological repositories for high-level radioactive waste (HLW) are dependent on the precise determination of the thermophysical parameters of mudstone. However, there is no relevant literature on the study of the thermophysical properties of Tamusu mudstone, a prospective rock for HLW disposal in China under the complex HLW disposal conditions. Therefore, in this paper, Tamusu mudstone is examined, and its thermophysical properties are tested at temperatures in the range of 25–80 °C with and without the influence of external forces. The thermophysical parameters exhibited significant anisotropic characteristics and were strongly correlated with temperature. The increase in temperature increases the specific heat capacity while lowering the thermal diffusivity. Due to the external force, the anisotropy of the thermophysical parameters decreases, enhancing the ability of the mudstone to transfer thermal energy. Furthermore, the aforementioned phenomena were interpreted from a microscopic perspective. This work can aid in the thermal-related physical phenomena of argillaceous rock and provide key input parameters for both analytical and numerical modeling in the safety assessment of HLW repositories, and other underground facilities at high temperatures.